Turnover, learning by doing, and the dynamics of productivity in Brazil - Leandro Pereira da Rocha; Valéria Lúcia Pero; Carlos Henrique Corseuil (EconomiA, 2019)
This article analyses the effect of labor turnover on the productivity of Brazilian manufacturing firms between 1996 and 2013. We based our analysis on a theory of learning by doing, where turnover harms productivity by restricting the efficiency gains achieved by workers when they accumulate learning by producing in the same firm. We estimate a learning measurement that takes into account the loss of human capital—resulting from turnover—and its effect on total factor productivity (TFP). Our learning measurement is shown to be robust and has a consistent positive relationship with three different estimates of TFP. Keywords: Learning by doing, Labor turnover, Produttivity